Incidence of injuries with the practice of active video games. - Perrier-Melo, Raphael José; Brito-Gomes, Jorge Luiz de; Fernandes, Matheus Santos de Sousa; Pereira, Sandro Vinicius Vidal de Negreiros; Costa, Manoel da Cunha (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: The active video games (AVGs) emerge in order to enhance the participation of physical activity (PA) in sedentary people. However, it has been seen that the practice is associated with the development of many lesions. Objectives: To present a review of the major injuries reported during and/or after the session with active video games. Method: The procedure of search of the literature was composed by two researchers independently (RJ) and (JL), in databases: Bireme®, PubMed®, Scopus® and Web of Knowledge®, between the years 2006 (year of creation and sales of Nintendo Wii) to 2014, only in the english language. Results: Initially identified 664 articles. However, after the selection criteria thirteen papers were selected and analyzed, all were performed with the console Nintendo Wii. Moreover, it can be noted that the games presented a framework of injury with the degree of light to vigorous. Being the major injuries around the shoulder joint and knee. Conclusion: The sports games especially Wii tennis and Wii bowling are the ones generated under higher incidence of injuries with the practice of active video games.